Use of thrombopoietin receptor agonists after hematopoietic progenitor cell transplantation. Issue 4 (26th July 2020) - Singer, Sara; William, Basem M.
Abstract: Hematopoietic stem cell transplant (HCT) is used with increasing frequency for the treatment of malignant and nonmalignant diseases. Thrombocytopenia is a common complication following HCT and is associated with decreased survival. Supportive care with platelet transfusion requires significant resources, reduces quality of life, and is associated with several adverse effects including transfusion reaction, infection, and alloimmunization. Thrombopoeitin receptor agonists (TPO‐RA) have been found to be safe and effective for the treatment of immune mediated thrombocytopenia, thrombocytopenia related to bone marrow failure syndromes, and thrombocytopenia of chronic liver disease. We hereby discuss in this review the evidence for use of TPO‐RA for the management of thrombocytopenia after HCT.